Estimation of Nitrogen Absorption of Rice Plants Based on Remote Sensing - Yanti, Delvi; Nurdiyanto, M. Rizki Dhani; Yanti, Nika Rahma; Syafii, Habibi Ahmad (Journal of Tropical Agricultural Engineering and Biosystems - Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2024)
One of the indicators of maintaining the quality of rice plants is monitoring and managing nitrogen requirements. Nitrogen (N) absorption in rice plants can be detected by remote sensing technology using Sentinel 2-A satellite imagery data using the NDRE (Normalized Difference Red Edge) method. This research aims to determine a mathematical model to predict nitrogen absorption in rice plants. This study uses the NDRE (Normalized Difference Red Edge) index value. The image used is Sentinel 2 imagery, namely channels 4 and 8 to see the Normalized Difference Vegetation Index (NDVI) value. Besides, the Normalized Difference Red-Edge Index (NDRE) is channels 5 and 8. The results of spatial and tabular data processing are analyzed per pixel and time trend to obtain patterns during one phase of the planting period. Based on the analysis of the NDVI and NDRE values of rice plants in Nagari Singkarak, the NDVI index pattern is in line with the NDRE index. At the beginning of planting (age ± 1 month) and the ripening period (age > ± 90 days) the NRDE value of rice plants is dominated by the low category NDRE value (red color). While when the rice is ± 60 days old, it is dominated by the high category NDRE value (green color). The estimation model for nitrogen uptake of rice plants in Nagari Singkarak based on NDRE data is y = 141.37 X + 0.0412, with a correlation coefficient (r) value of 0.97, which indicates a high correlation between NDRE values and nitrogen uptake.